Zinc application improves growth, yield and grain zinc concentration of mung bean (Vigna radiata L.) - Mubshar Hussain; Muhammad Zeeshan Shahid; Noman Mehboob; Waqas Ahmed Minhas; Muhammad Akram (Semina: Ciências Agrárias, 2021)
Minerals’ deficiency, including iodine (I), vitamin A, iron (Fe) and zinc (Zn) is a widespread threat to mankind. Around 2 billion people (children, women, and people of middle age group) across the globe suffer from mineral deficiencies. The productivity of mung bean is very low in arid and semi-arid regions due to little or no application of fertilizers. Majority of mung bean growing regions of Pakistan have low Zn concentration in soils. This study evaluated the impact of different Zn sources and their application methods on allometry, yield and grain biofortification of mung bean. Mung bean variety “Azri 2006” was used as experimental material. Three different Zn sources, i.e., zinc sulfate (ZnSO4), Zn-EDDHA and 50 % ZnSO4 + 50% Zn EDDHA. Application method included in the study was basal application, foliar application and 50% basal + 50% foliar application. The results indicated that Zn application improved allometric traits and productivity of mungbean. The ZnSO4 source of Zn with basal application resulted in the highest chlorophyll contents, leaf area index, number of sympodial and monopodial branches, and number of pods per plant, 1000-seeds weight, biological yield and seed yield as compared to control treatment. In conclusion, 10 kg ha-1 Zn application as basal application method seemed a viable option to improve mung bean productivity along with higher grain Zn biofortification.